Insulin resistance as a mediator in the association between nickel exposure and metabolic dysfunction-associated steatotic liver disease - Zhou Liu; Liang Zhang; Yanrui Wu; Zongbiao Tan; Guang Li; Zhenwen Li; Liying Zhan; Weiguo Dong (Diabetology & Metabolic Syndrome)
Abstract Background The myriad implications of heavy metal pollution on human health have garnered substantial attention within the academic domain. Nevertheless, a notable research gap persists, as there is currently insufficient direct investigation elucidating the intricate interplay between nickel exposure and the risk of metabolic dysfunction-associated steatotic liver disease (MASLD). Methods The data utilized in this study was sourced from the National Health and Nutrition Examination Survey 2017–2020. Hepatic steatosis was evaluated utilizing controlled attenuation parameters (CAP), and nickel exposure level was reflected by urinary nickel concentration. To analyze the association between nickel exposure and MASLD, three multiple logistic regression models with weights were developed. Furthermore, a mediation analysis was performed to examine insulin resistance’s potential mediating role. Results There were a total of 1,187 participants in the study, of which 548 (46.17%) had MASLD. MASLD individuals had a significantly higher urinary nickel concentration than non-MASLD individuals (P = 0.008). After accounting for demographic factors, biochemical indicators, and metabolic conditions, the odds ratio (OR) and 95% confidence interval (CI) for MASLD were 2.10 (1.09–4.05) per onefold increase in urinary nickel concentration and 2.61 (1.22–5.55) for the highest tertile versus the lowest tertile. Insulin resistance was found to mediate approximately 73.69% of the total association between nickel exposure and MASLD (P = 0.004). Conclusions Nickel exposure was independently associated with the prevalence of MASLD. Excessive exposure to nickel may promote the occurrence of MASLD by enhancing insulin resistance.